Effect Analysis on Combustion and Emission Characteristics of a Rotary Burner Fueled by Biomass Pellet Fuel - Guohai Jia; Lijun Li; D. M. Zhang (Journal of Chemistry)
A biomass pellet rotary burner was chosen as the research object, in order to study the influence of excess air coefficient on the combustion phenomenon of biomass rotary burner, the finite element simulation model of a biomass rotary burner was established, and simulation results of a biomass rotary burner were verified by the experiment. The computational fluid dynamics software was applied to simulate the combustion characteristics of biomass rotary burner in a steady-state condition, and the effect of excess air coefficient on temperature field and component concentration field in biomass rotary burner was analyzed. The results show that the flue gas flow rate inside the burner gradually increases with the increase of air velocity, the area with large temperature is mainly concentrated in the middle region of the rotary burner, and the maximum combustion temperature also appeared in the middle region of the combustion chamber, and the formation area of CO decreases with the increase of excess air coefficient. CO2 is mainly concentrated in the middle region of the burner, and the CO2 generating region decreases with the increase of excess air coefficient. The experimental value of the combustion temperature of the biomass rotary burner is in good agreement with the simulation results.